A novel liquid-based battery thermal management system coupling with phase change material and thermoelectric cooling. (1st August 2023) - Pakrouh, R.; Hosseini, M.J.; Ranjbar, A.A.; Rahimi, M.
Abstract: The present study experimentally investigates a novel type of battery thermal management system that works based on water cooling and thermoelectric cooling (Peltier effect). In the current proposed system, water cooling is targeted by a number of thermoelectric coolers (TEC) and the temperature of the hot side of the TECs is controlled by the RT35 phase change material (PCM). To conduct a comparison, the results are compared with the case in which the hot side of the TECs' temperature is managed using forced convection (FC) driven by fans. Moreover, the variations of TECs number, assuming constant applied power are examined. Results indicated that the thermoelectric module is considerably effective on controlling the battery pack temperature. Such that, after 90 min of the initiation of the experiment, the cases of 2TEC which benefit from FC and PCM reduce the battery pack temperature 11.3 °C and 17.75 °C respectively in comparison with the system without a cooling device. The obtained results show that the implementation of PCM in comparison with FC is more effective on controlling the temperature of the battery pack simulator (BPS). In other words, the temperatures of the battery pack for the PCM cases are 4.1 °C to 12.64 °C lower than that of the corresponding FC cases. Results also indicated that the coefficient of performance of the system is proportionally related to the number of the cooling modules and is inversely affected when the applied power to the thermoelectric module rises. Results also revealed that among the cases, in 14 conditions the temperature of the battery pack lowers to a value <40°C; 9 cases of which contains PCM and 5 systems benefits from FC cooling. The best case among the studied ones is 3TEC/P2/PCM which suggests maximum battery temperature of 37.8 °C, 12.4 W power consumption and 3.23 coefficient of performance. Highlights: A novel hybrid liquid-TEC-PCM for battery thermal management is introduced. Results compared with the case of forced convection cooling of TECs. PCM is more effective than that of forced convection. The best case is providing 37.8 °C maximum temperature and 3.23 COP.